Modelling in vitro gametogenesis using induced pluripotent stem cells: a review - Maria Victoria Romualdez-Tan (Cell Regeneration, 2023)
Abstract In vitro gametogenesis (IVG) has been a topic of great interest in recent years not only because it allows for further exploration of mechanisms of germ cell development, but also because of its prospect for innovative medical applications especially for the treatment of infertility. Elucidation of the mechanisms underlying gamete development in vivo has inspired scientists to attempt to recapitulate the entire process of gametogenesis in vitro. While earlier studies have established IVG methods largely using pluripotent stem cells of embryonic origin, the scarcity of sources for these cells and the ethical issues involved in their use are serious limitations to the progress of IVG research especially in humans. However, with the emergence of induced pluripotent stem cells (iPSCs) due to the revolutionary discovery of dedifferentiation and reprogramming factors, IVG research has progressed remarkably in the last decade. This paper extensively reviews developments in IVG using iPSCs. First, the paper presents key concepts from groundwork studies on IVG including earlier researches demonstrating that IVG methods using embryonic stem cells (ESCs) also apply when using iPSCs. Techniques for the derivation of iPSCs are briefly discussed, highlighting the importance of generating transgene-free iPSCs with a high capacity for germline transmission to improve efficacy when used for IVG. The main part of the paper discusses recent advances in IVG research using iPSCs in various stages of gametogenesis. In addition, current clinical applications of IVG are presented, and potential future applications are discussed. Although IVG is still faced with many challenges in terms of technical issues, as well as efficacy and safety, novel IVG methodologies are emerging, and IVG using iPSCs may usher in the next era of reproductive medicine sooner than expected. This raises both ethical and social concerns and calls for the scientific community to cautiously develop IVG technology to ensure it is not only efficacious but also safe and adheres to social and ethical norms.